PERMASALAHAN DAN STRATEGI PEMECAHAN MASALAH NELAYAN TRADISIONAL KELURAHAN BAGAN DELI KECAMATAN MEDAN BELAWAN KOTA MEDAN PROPINSI SUMATERA UTARA - Kusbianto, Dr; Simon, John; Irwanmay, Irwanmay (Jurnal Ilmiah Advokasi, 2021)
Fishermen are used to be in poverty or otherwise, that relates to them called the poorest of the poor. Indonesia is a maritime country whose about two-thirds of the total sea area with a full coastline length is 99,093 km. It classifies the traditional fishermen as a group of people in poverty with a height level of reliance on fishery resources. The study started in Bagan Deli Village, Medan Belawan District, Medan City, North Sumatra Province. This research aims to find the issues that exist in them and resolving for them. The study uses a survey method with interview techniques. The fishermen of the respondents determine by the purposive method by the number of 43 people. Data analyzed in the Likert scale, which is to measures the perceptions, attitudes, and opinions by the respondents about an occurrence or their social phenomenon in Bagan Deli that keep in a questionnaire form. The results show that 13 questions ask respondents that defines all agreed, except for the questionnaire statements number 13 and 4 are Strongly Agree. Statement number 13 is ‘Do you agree if a fishery product processing in business group establishes in the Bagan Deli fishing environment?’ That is the highest-ranking with a total weight of 145, and the result is a score of 84.30% with an interpretation of the score Very Strong (Strongly Agree). The questionnaire for number 4 is 'Does environmental pollution cause a decrease in fishing and other types of fishing?', the second highest-ranking with a total weight of 138. And the result is 80.23% with an interpretation of the score Very Strong (Very Agree).Keyword : traditional fishermen, problems